Characterization of the Expression and Regulation of Genes Necessary for myo-Inositol Biosynthesis and Transport in the Seminiferous Epithelium1 - Theodore R. Chauvin; Michael D. Griswold (2004)
In many mammals, the concentration of myo-inositol in the fluid of the seminiferous tubules is dramatically higher than levels found in serum. Two enzymes involved in myo-inositol synthesis: myo-inositol-1-phosphate synthase (ISYNA1) and myo-inositol monophosphatase-1 (IMPA1), are known to have high activity in the testes. ISYNA1 is an isomerase that catalyzes the conversion of glucose-6-phoshate to myo-inositol-1-phosphate. IMPA1 then hydrolyzes the phosphate group to produce myo-inositol. Although no physiological role for the high concentration of myo-inositol has yet to be elucidated, it has been suggested that it could be involved in osmoregulation. Previous research on these enzymes in the testis has focused on enzyme activity. The objective of this study was to evaluate the expression of these genes and the myo-inositol transporter, Slc5a3, within the testis. Using Northern blot analyses, we found that all three genes, Impa1, Isyna1, and Slc5a3 are expressed in Sertoli cells. Isyna1 is highly expressed in two types of germ cells, pachytene spermatocytes and round spermatids. IMPA1 was expressed in round spermatids. Slc5a3 expression is upregulated when Sertoli cells are treated with 0.1 mM dibutyryl cAMP. When Sertoli cells were cultured in a hypertonic medium, there was an increase in the expression of Isyna1 and Slc5a3. We postulate that this upregulation is a result of the capability of the Sertoli cell to sense and then react to a change in osmolarity by increasing the transport and production of the osmolyte myo-inositol.